Ethnic disparity in primary cutaneous CD30+ T‐cell lymphoproliferative disorders: an analysis of 1496 cases from the US National Cancer Database. (20th April 2018) - Su, Chang; Nguyen, Kevin A.; Bai, Harrison X.; Zogg, Cheryl K.; Cao, Ya; Karakousis, Giorgos; Zhang, Paul J.; Zhang, Guiying; Xiao, Rong
Summary: Primary cutaneous CD30 + T cell lymphoproliferative disorders (PCLPD), the second most common type of primary cutaneous T cell lymphomas, accounts for approximately 25–30% of cutaneous T‐cell lymphoma cases. However, only small retrospective studies have been reported. We aimed to identify prognostic factors and evaluate the overall survival (OS) of patients with PCLPD stratified by ethnicity. We identified 1496 patients diagnosed with PCLPD between 2004 and 2014 in the US National Cancer Database. Chi‐square test andanova were used to evaluate differences in demographic and disease characteristics, socioeconomic factors and treatments received. OS was evaluated with the log‐rank test, Cox proportional hazard regression analysis, and propensity score matching. The study included 1267 Caucasians, 153 African Americans (AA), 43 Asians, and 33 of other/unknown ethnicity. Older age, higher Charlson‐Deyo score, higher clinical stage and receipt of chemotherapy were predictors of shorter OS. Primary disease site on a lower extremity was associated with shorter OS, while a head and neck location was associated with longer OS. AA patients had shorter OS when compared to Caucasian patients on multivariate analysis. This ethnic disparity persisted on propensity‐score matched analysis and after matching Caucasian and AA patients on demographic and disease characteristics, socioeconomic factors and treatments received, and age and gender‐matched relative survival analyses.